2006
DOI: 10.1186/1471-2482-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of blood inflammatory markers for detection of acute appendicitis in children

Abstract: Background: Acute appendicitis (AA) is a common surgical problem that is associated with an acute-phase reaction. Previous studies have shown that cytokines and acute-phase proteins are activated and may serve as indicators for the severity of appendicitis. The aim of this study was to compare diagnostic value of different serum inflammatory markers in detection of phlegmonous or perforated appendicitis in children.Methods: Data were collected prospectively on 211 consecutive children. Laparotomy was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
4
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 15 publications
(20 reference statements)
8
78
4
8
Order By: Relevance
“…However, when WBC of group with early appendicitis (mucosal ulceration and focal appendicitis) was compared that of group with abdominal pain who did not require surgery, no statistically significant difference was found (p>0.05). [14] In the present study, results were similar to those reported in the literature.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, when WBC of group with early appendicitis (mucosal ulceration and focal appendicitis) was compared that of group with abdominal pain who did not require surgery, no statistically significant difference was found (p>0.05). [14] In the present study, results were similar to those reported in the literature.…”
Section: Discussionsupporting
confidence: 83%
“…They found that CRP was significantly higher in group with PA (p<0.001). [14] In the same study, ESR level was also higher in group with appendicitis. In the current study, CRP and ESR values were also statistically significantly higher in patients with appendicitis, compared with control subjects.…”
Section: Discussionsupporting
confidence: 52%
“…In particular, increased neutrophil count may be accepted as a useful marker to indicate level of inflammation in diagnosis of acute appendicitis. [10][11][12] As in the literature, the present study also found that the difference in serum IL-6 levels tested preoperatively between Group 1 patients (65.7±6.3 pg/mL), who had laparoscopic appendectomy, and Group 2 patients (65.2±4.7 pg/mL), who underwent conventional appendectomy, was low and statistically insignificant (p=0.752). The serum IL-6 levels tested at postoperative 24 th hour in both groups (76.1±16.1 pg/mL in Group 1 and 105.2±16.1 pg/mL in Group 2) were remarkably high, especially in the conventional surgery patients, and the finding was statistically extremely significant (p<0.001).…”
Section: Discussionsupporting
confidence: 68%
“…Adanya perubahan sintesis protein ini dapat menimbulkan respon tubuh berupa tingginya kadar leukosit darah serta peningkatan aktivitas imun dan suhu tubuh. [19,20,21] Penelitian ini juga menunjukkan bahwa SD memiliki hubungan yang bermakna dengan kejadian apendisitis perforasi.…”
Section: Pendahuluanunclassified